The hidden kingdom eaudiobook - Sutherland, Tui T. (Wings of Fire, 2017)
The WINGS OF FIRE saga continues! Deep in the rain forest, danger awaits...Glory knows the dragon world is wrong about her tribe. After all, she isn't "as lazy as a RainWing" — she isn't lazy at all! Maybe she wasn't meant to be one of the dragonets of destiny, as the older dragons constantly remind her, but Glory is sharp and her venom is deadly... except, of course, no one knows it.When the dragonets seek shelter in the rain forest, Glory is devastated to find that the treetops are full of RainWings that no dragon could ever call dangerous. They nap all day and know nothing of the rest of Pyrrhia. Worst of all, they don't realize — or care — that RainWings are going missing from their beautiful forest. But Glory and the dragonets are determined to find the missing dragons, even if it drags the peaceful RainWing kingdom where they never wanted to be — in the middle of the war.